2020
DOI: 10.3390/cells9102179
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Bone Morphogenetic Proteins 2 and 4 in Patients with Acute Myocardial Infarction

Abstract: Background: Bone morphogenetic proteins-2 and -4 (BMPs) have been implicated in left ventricular remodeling (LVR) processes such as an inflammation and fibrogenesis. We hypothesized that this knowledge could be translated into clinics. Methods: We studied the dynamics of serum levels of BMPs, its correlation with markers of LVR and with parameters of echocardiography in patients (n = 31) during the six-month follow-up period after myocardial infarction (MI). Results: Elevated serum levels of BMPs decreased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…One research reported that patients’ BMP4 serum levels were elevated after myocardial infarction. 27 The BMP4 elevation lasted for about 14 days and was correlated with left ventricular remodeling. 27 Another study furtherly proved that BMP4 plasma levels in patients suffering from out-of-hospital cardiac arrest were significantly higher than patients with stable coronary artery disease or healthy volunteers, accompanied by increased mortality and unfavorable neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One research reported that patients’ BMP4 serum levels were elevated after myocardial infarction. 27 The BMP4 elevation lasted for about 14 days and was correlated with left ventricular remodeling. 27 Another study furtherly proved that BMP4 plasma levels in patients suffering from out-of-hospital cardiac arrest were significantly higher than patients with stable coronary artery disease or healthy volunteers, accompanied by increased mortality and unfavorable neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 27 The BMP4 elevation lasted for about 14 days and was correlated with left ventricular remodeling. 27 Another study furtherly proved that BMP4 plasma levels in patients suffering from out-of-hospital cardiac arrest were significantly higher than patients with stable coronary artery disease or healthy volunteers, accompanied by increased mortality and unfavorable neurological outcomes. 28 Remarkably, the serum from patients undergoing myocardial infarction and post-resuscitation was found to induce endothelial dysfunction via activating the BMP4 signaling pathway and to exert pro-inflammatory properties in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Нами было выявлено присутствие в тканях почек у больных ИМ мф как 1-го, так и 2-го фенотипов в ранние и отдаленные сроки ИМ. Известно, что макрофагальный состав почки в норме представлен в основном тканевыми мф, обладающими противовоспалительным фенотипом (М2) и осуществляющими функцию фагоцитоза и поддержания гомеостаза [17]. При истощении пула тканевых мф в результате ИМ происходит их пополнение пришлыми мф.…”
Section: Discussionunclassified
“…Moreover, in case of the most common ischemic HF, there is a loss of LV function as a result of ischemic damage to the myocardial tissue and LV remodeling [5]. Chronic myocardial ischemia causes a vicious circle, activating compensatory neurohormonal and inflammatory mechanisms [6,7], leading to the progression of HF, and resulting in ischemic cardiomyopathy. The use of optimal pharmacological and surgical treatment improved the survival rate of patients with HF during the period from 1979 to 2000 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studying the inflammatory response as a fundamental link in the pathogenesis of HF and as the main component of HF decompensation is currently of a particular interest. The elimination of myocardial ischemia is not associated with a decrease in the incidence of HF whereas the proportion of patients with adverse cardiac remodeling remains high [7,8]. Over time, there was a transition of views in regard to chronic and physiological inflammation occurring in response to any tissue damage (myocardial ischemia, hypertension, etc.…”
Section: Introductionmentioning
confidence: 99%